Graphene Emerges as a Versatile Template for Materials Preparation. Issue 20 (5th April 2016) - Li, Zhengjie; Wu, Sida; Lv, Wei; Shao, Jiao‐Jing; Kang, Feiyu; Yang, Quan‐Hong
Abstract : Graphene and its derivatives are emerging as a class of novel but versatile templates for the controlled preparation and functionalization of materials. In this paper a conceptual review on graphene‐based templates is given, highlighting their versatile roles in materials preparation. Graphene is capable of acting as a low‐dimensional hard template, where its two‐dimensional morphology directs the formation of novel nanostructures. Graphene oxide and other functionalized graphenes are amphiphilic and may be seen as soft templates for formatting the growth or inducing the controlled assembly of nanostructures. In addition, nanospaces in restacked graphene can be used for confining the growth of sheet‐like nanostructures, and assemblies of interlinked graphenes can behave either as skeletons for the formation of composite materials or as sacrificial templates for novel materials with a controlled network structure. In summary, flexible graphene and its derivatives together with an increasing number of assembled structures show great potentials as templates for materials production. Many challenges remain, for example precise structural control of such novel templates and the removal of the non‐functional remaining templates. Abstract : A conceptual review on graphene‐based templates is given, highlighting their versatile roles in materials preparation, as soft or hard templates, as nucleation or orientation substrates directing nanostructure growth, as pre‐ or post‐restacked space for the confined growth of 2D nanostructures, and, as supporting skeletons and sacrificial templates for replicating assembled graphene for functional materials.